Laboratory spawning of the purple snail Plicopurpura pansa (Gastropoda: Muricidae) - Naegel, Ludwig C. (2004)
The spawning of the muricid gastropod Plicopurpura pansa in the laboratory at 22-23°C is described. Females deposited 1-20 capsules daily for at least 20 weeks, and produced up to 150 capsules each per spawning season. During spawning, egg clusters were formed consisting of hundreds of capsules of different ages deposited by different females. Each egg capsule contained an average of 436 embryos (± s.d. 213.6, range: 95- 1 092, n = 50). Embryos developed without nurse eggs. After six to eight weeks of intracapsular, lecithotrophic development, planktotrophic veligers hatched with two fully developed velar lobes